1991
DOI: 10.3354/meps078097
|View full text |Cite
|
Sign up to set email alerts
|

Sulfate-reducing bacteria in temporarily oxic sediments with bivalves

Abstract: Under seasonally fluctuating redox conditions in sediment of Kiel Bay (eastern Baltic Sea), viable counts (MPN) of sulfate-reducing bacteria (SRB) ranged between 4 X 102 and 7 X 104 cm-3 These MPN appeared fairly independent of ambient redox potentials and followed peaks of phytoplankton productivity in the water column with a time lag of 2 to 3 wk. The relative proportions of SRB using acetate, lactate or succinate as their electron donors fluctuated widely. Shells of the clam Arctica islandfca, which can sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

1995
1995
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 22 publications
0
9
0
Order By: Relevance
“…comm.). Due to the high competition of other thiosulphate-oxidizing bacteria with higher growth rates, it is suggested that these bacteria are commensals which have found a niche inside the carapax of C. torosa where they can directly use the thiosulphate produced by the ostracods as an energy source, comparable, e.g., to succinate utilization by sulphate-reducing bacteria on the shells of the clam Arctica islandica (Bussmann & Reichardt 1991). Due to slower growth and lower thiosulphate oxidation rate at hypoxia and probably the lack of nitrate as electron acceptor (A. Schneider pers.…”
Section: Discussionmentioning
confidence: 99%
“…comm.). Due to the high competition of other thiosulphate-oxidizing bacteria with higher growth rates, it is suggested that these bacteria are commensals which have found a niche inside the carapax of C. torosa where they can directly use the thiosulphate produced by the ostracods as an energy source, comparable, e.g., to succinate utilization by sulphate-reducing bacteria on the shells of the clam Arctica islandica (Bussmann & Reichardt 1991). Due to slower growth and lower thiosulphate oxidation rate at hypoxia and probably the lack of nitrate as electron acceptor (A. Schneider pers.…”
Section: Discussionmentioning
confidence: 99%
“…Bacteria that would react with the probe specific for Desulfobacter were not present. Shells of the clam Artica islandica from sediments were colonized by epizoic SRB (Bussmann and Reichardt, 1991). These clams can survive anoxia and it was suggested that bound bacteria had high biogeochemical activity.…”
Section: Interactions With Plants and Animalsmentioning
confidence: 99%
“…Mucin, a sulfated polysaccharide, can serve as the source of sulfate for the bacteria in the human large gut ; the release of sulfate from mucin for the growth of SRB is attributed to enzymes from Bacteroides residing in the gut (Tsai et at., 1992). Diet strongly influences the type of bacteria in the human large intestine: when sulfate is available SRB are abundant, Gibson et al, 1991Widdal and Pfennig, 1984Widdal and Pfennig, 1984Widdal and Pfennig, 1984Widdal and Pfennig, 1984Campbell and Singleton, 1986Trinkerl et aI., 1990Bauman et al, 1990Fenchel and Ramsing, 1992Bussmann and Reichardt, 1991 but when sulfate is limiting, methanogens are abundant (Christl et ai., 1992). Species of bacteria belonging to the genera of Desulfovibrio and Desulfobulbus account for consumption of H2 in the intestine and represent 66% and 16%, respectively, of all colony-producing SRB (Gibson et al, 1993).…”
Section: Interactions With Plants and Animalsmentioning
confidence: 99%
“…This is due in part to the fact that ventilation and oxic conditions occur only intermittently (e.g. Scott 1975, AUer 1982, Kristensen 1988, Bussman & Reichardt 1991. In the case of denitrification, enhanced activity is due to increased nitrate availability from nitrification during oxic periods and close coupling between these processes (Blackburn et al 1994).…”
Section: Introductionmentioning
confidence: 99%